A checklist of cephalopods from continental shelf of Sarawak, Malaysian Borneo - Wan Morni, Wan Zabidii; Hassan, Ruhana; Abit, Lirong Yu; Latif, Kamil (Society for Indonesian Biodiversity, 2022)
Cephalopods can be discovered in all the oceans of the world ranging from shallow to deep oceans. It is a naturally inhabited seawater medium and indirectly limits the number of research regarding the species composition of the cephalopods group. Previously, samples of cephalopods were collected from selected stations in Sarawak Exclusive Economic Zone (EEZ) using an otter trawl net with a stretch mesh size of 38 mm at the cod end. All samples used in this study were the by-catch of trawling activities during National Demersal Fish Resource Survey in Sarawak (16 August until 6 October 2015). Trawling operations were conducted beyond 12 nautical miles from the coast, and the area was divided into three depth strata, I) 20-50 m; II) 50-100 m; and III) 100-200 m. In total, 16 species of cephalopods were found to inhabit Sarawak waters, representing five families and eight genera. The present findings found that there was a higher number of species recorded in-depth strata I (14 species) in comparison to strata II (12 species) and III (11 species). Six species of the cephalopods captured in this study were the first recorded in Malaysian water, namely Amphioctopus marginatus, Amphioctopus rex, Ommastrephes bartramii, Sepia brevimana, Sepia vietnamica and Sepia prashadi. Thus, the information on cephalopod diversity and distribution at different depth strata will be useful for updating the current database on Malaysian marine species diversity.